THE CHOICE OF DISTRIBUTION METHOD OF COLLECTIVE INCOME BETWEEN THE TEAM MEMBERS ON A METALLURGICAL PLANT - Hordienko, V. O. (Science and Transport Progress, 2007)
Recommendations on the use of the most widespread methods of distributing of collective earnings between the members of production brigades in the conditions of metallurgical enterprises are developed.